2008
DOI: 10.2323/jgam.54.51
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of lactic acid bacteria isolated from Tibetan Qula cheese

Abstract: Fourteen strains of Lactic Acid Bacteria (LAB) isolated from Qula, a Tibetan traditional yak cheese, were divided into four groups (A-D) according to morphological and biochemical characteristics. On the basis of the 16S rRNA gene sequence analysis, group A and group B strains were placed in the cluster making up the genus Leuconostoc, which together with Leuconostoc mesenteroides and Leuconostoc pseudomesenteroides, formed a distinct cluster. The group C strain was clearly identified as Enterococcus faecium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 32 publications
(30 reference statements)
1
57
3
Order By: Relevance
“…However, S. thermophilus dominated, contributing to 33% of all cocci isolates. Bao et al (2012) also reported that S. thermophilus was the dominating species in Qula cheese (39%), whereas Tan et al (2010) and Duan et al (2008) reported that the dominating LAB was the Leuconostoc species (86% and 78%, respectively).…”
Section: Enumeration Isolation and Identification Of Lab From Qula Cmentioning
confidence: 99%
See 1 more Smart Citation
“…However, S. thermophilus dominated, contributing to 33% of all cocci isolates. Bao et al (2012) also reported that S. thermophilus was the dominating species in Qula cheese (39%), whereas Tan et al (2010) and Duan et al (2008) reported that the dominating LAB was the Leuconostoc species (86% and 78%, respectively).…”
Section: Enumeration Isolation and Identification Of Lab From Qula Cmentioning
confidence: 99%
“…In particular, LAB plays an essential role in the formation of the aroma, texture, and acidity of the products. Previous studies showed that LAB is the dominant species in the microorganisms of Qula cheese, and play the most important role in the accumulation of nutrients (Bao et al, 2012;Duan et al, 2008). Some of the lactic acid bacteria are also known to have beneficial effects on human health (Mohd Adnan and Tan, 2007;Zhang, W. Y. et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…All members are Gram-stain-positive, catalase-negative, non-motile, non-spore-forming bacteria. Bacteria of the genus Lactococcus are widely distributed in a variety of fermented foods, dairy products, and plant and animal materials (Schleifer et al, 1985;Williams et al, 1990;Chen et al, 2001Chen et al, , 2014Duan et al, 2008). They have also been reported to be one of the most important lactic acid bacteria in the hindgut of wood-feeding termites (Bauer et al, 2000).…”
mentioning
confidence: 99%
“…So, herders usually heat raw milk, and add an appropriate amount of kurut as a starter into cooled processed milk, and then allow the mixture to undergo fermentation naturally into kurut. If the kurut can be separated from whey and then dried, it becomes qula, which is usually a granular dried kurut solid without a shaping process (Duan et al, 2008). By the above processes, various kinds of fermented milks and derived products were produced using naturally occurring LAB developed in Gansu, each with its own characteristic history.…”
Section: Discussionmentioning
confidence: 99%
“…and many traditional dairy products like fermented yak milk, fermented goat milk, koumiss, butter, cheese, kefi r, whey and qula (Badis et al, 2004;Chena et al, 2008;Duan et al, 2008;Kongo et al, 2007;Liu et al, 2009;Ouadghiri et al, 2005;Watanabe et al, 2008;Zhang et al, 2008a, b). Therefore, more and more basic work on isolation, genotypic and phenotypic studies was applied to wild LAB, which were isolated from raw milk and traditional fermented dairy products (Cogan et al, 1997;Wouters et al, 2002).…”
mentioning
confidence: 99%